A systematic review of new treatments for cryptoglandular fistula in ano. Issue 1 (February 2017) - Narang, Sunil K.; Keogh, Kenneth; Alam, Nasra N.; Pathak, Samir; Daniels, Ian R.; Smart, Neil J.
Abstract: Aim: In 2007 the ACPGBI published a position statement on the management of cryptoglandular fistula in ano. Over the last seven years a number of new treatments have been developed and the aim of this systematic review was to assess their effectiveness. Method: A systematic review of all English language literature relevant to novel treatment strategies for cryptoglandular fistula in ano, published between 1 January 2007 and 31 Dec 2014 was carried out using MEDLINE (PubMed and Ovid), EMBASE (Ovid) and the Cochrane Library of Systematic Reviews/Controlled Trials for relevant literature. Technical notes, commentaries, letters and meeting abstracts were excluded. The different treatments were assessed with regards to fistula closure rate in relation to length of follow up and reported complications. Results: Seventy potential articles published between 1 January 2007 and 31 December 2014 were identified from the initial literature search. Twenty-one articles were included for final analysis although only two were randomized controlled trials, the remainder being retrospective or prospective series. Conclusion: This systematic review has demonstrated that whilst there have been technological advances to treat complex cryptoglandular fistula in ano, these are in an early stage of evolution and although early results were promising they are difficult to reproduce. Longer follow up data is not currently available and these treatments should not be introduced without further evidence.